Brunswick bowling & billiards / Nurfatin Amirah Amir Hamzah - Amir Hamzah, Nurfatin Amirah (2020)
Brunswick Bowling & Billiards was the business segment of Brunswick Corporation that historically encompassed the following three divisions which is Billiards, Bowling centre and Bowling equipment and products. Brunswick's global headquarters is in the northern Chicago suburb of Mettawa, Illinois. One of the products that produce by this company is bowling bag. This product has two types which is carry bag and roller bag. The design of the bag is based on the capacity ball. Different capacity ball has different design. The purpose of this study are to analyse the problem that Brunswick Company faced and provide solution to overcome the problem. After doing company analysis, there are several problems about bowling bag. The problems are difficult to handle, less compartment and not have safety lock. Furthermore, there are some features that not suitable for some categories players such as the extending handle is short and make the taller people difficult to move. From this problem, there are some suggested and recommendation to overcome this problem. The company should innovate or make a changes design about their product to fulfil the customer satisfaction towards their product.